Termos botânicos - Rocha, Arildo Bueno [UNESP] (Sociedade Brasileira de Farmacognosia, 1986)
Há termos botânicos que são heterofônicos. O significado e a perfeita prosadia doles obém-se em linguagem científica, através da etimologia. Como exemplo,encontram-se mesofilo e mesófilo. Este, sendo proparoxítono, refere-se aquilo que vive em lugares de luz difusa e umidade média; e aquale, referindo-se a anatomia da folha, é paroxítono. Com relação ao termo taxinomia, formado pelos prefixos gregos taxi e namo e mais o sufixo -ia, não deixa de ser a melhor combinação e deve-se, portanto, rejeitar as formas paralelas de taxeonomia, taxionomia e taxonomia.

On portuguese there are some words used in botany that can have one form and two different meanings, according to the way the word is pronounced or accented. It is through the study of the ethimology of those words that we come to use the right word its pronunciation in order to use (put) the scientific terminology correctly. As an example, we have the word mesofilo that can have two different accents: 1) mesofilo (no graphic accent in writing, only in pronunciation) that has its correspondent mesophyll in English; 2) mesófilo (graphic accent) that its correspondent mesophyte in English. As to the word taxonomy there has been a discussion about how the word should be written: taxeonomia, taxionomia and taxonomia, the latter being the most frequent. Our intention is reverse the process. According to our studies, this word comes from the greek prefixes: táxi- and nómo- plus the suffixe ia. So, we propose the therm taxinomia that is best combination and we are trying to reject all the other forms.
Botanical terms
Keywords: mesofilo; mesófilo; taxinomia (taxonomia, taxionomia, taxeonomia); mesófilo = mesophyte; taxinomia= taxonomy (taxonomia, taxeonomia e taxionomia)